The Addie Model on the Development English Materials for the Constitutional Law Study Program - Syam, Andi Tenrisanna; Ermawati, Ermawati (Universitas Negeri Semarang, 2024)
This research aimed at developing appropriate and valid English materials for the Constitutional Law Study Program and finding out the students’ perception of the English materials. The writers applied Research and Development by adopting the ADDIE model. 95 students of the Constitutional Law Study Program at IAIN Palopo filled out a need analysis questionnaire, four experts assessed the English materials, and 24 students participated in the field try-out. The instruments of this research were questionnaires and documentation. The writers analyzed the data from questionnaires quantitatively and qualitatively. The writers produced an English textbook and generated it into a flipbook. There are ten units in the textbook. The results of the content, the design, and the media experts’ validation showed that the book got an excellent and a good category. The book quality based on the learners’ response in the field try-out showed that learners agreed with the materials presented in the book.